Japan and China in Southeast Asia: Political Dimension - E S Martynova (Vestnik RUDN International Relations, 2013)
The article is focused on the research of the policy of Japan and China in Southeast Asia at the present stage. The paper analyses the process of establishment and subsequent development of the “ASEAN Plus Three” (APT) framework, which includes ten countries of ASEAN and the three Northeast Asian states of China, Japan and South Korea. “ASEAN Plus Three” might serve as catalyst for the processes of economic and political integration in East Asia. The rivalry of China and Japan is a major constraint to the development of integration structures. Our analysis suggests that China is the regional leader in East and Southeast Asia at the moment.